G153 Type 2 diabetes in children and young people in UK and republic of ireland. (24th May 2017) - Candler, TP; Mahmoud, O; Barrett, TG; Hamilton-Shield, JP
Abstract : Aims: To estimate the incidence of type 2 diabetes in children under 17 years of age in the UK and Republic of Ireland and characterise the clinical features and co-morbidities present at diagnosis. In 2005, the incidence in the UK of type 2 diabetes in children under 17 years of age was 0.53/100, 000/year. Methods: Using the British Paediatric Surveillance Unit reporting framework, cases of type 2 diabetes diagnosed in children under 17 years of age in the UK and Republic of Ireland between 1 st April 2015 and 30th April 2016 were reported each month. Results: One hundred and five cases of type 2 diabetes were identified, giving a UK incidence of 0.72/100, 000/year(95% CI 0.58–0.88). Children from ethnic minorities had a significantly higher incidence of type 2 diabetes compared with white children (0.43/ 100, 000/year) with incidences of 2.92/100, 000/year ( sevenfold) and 1.67/100, 000/year ( four-fold), in Asian and Black children respectively. Sixty-six percent of cases were female and 81% had a family history of type 2 diabetes. Thirty-four percent were asymptomatic at diagnosis. Fifty-three percent had osmotic symptoms of diabetes (polyuria, polydipsia, weight loss), 18% had recurrent infections with vulvo-vaginitis frequently reported. Thirty-seven percent had fatty liver disease and 21% were hypertensive at diagnosis. Conclusions: Type 2 diabetes is relatively rare in the UK but the incidence is rising when compared with the last 2004/5 BPSU survey. Children from ethnic minorities are significantly over represented compared with white children. Female sex, obesity and family history are strongly associated with the type 2 diabetes in this age group.